Model Resapan Mekanik Kuantum Zarah Bebas dalam Selang Terbatas - Mohamad Zain, Shaharir; Yaacob, Nik Rusdi (Universiti Putra Malaysia Press, 2002)
According to the standard interpretation of quantum mechanics (Born and Bohr-Copenhagen interpretations), the square of the magnitude of the wave function represents a probability density function for a particle in a state whereby a measurement is made on it. In this article it is shown that a quantum particle which is classically a free particle in a bounded interval with mass 711, has its wave function whose square modulus satisfies a diffusion equation